Tiny Sips and Walmart—A Dream or a Curse?. (November 2021) - Boyle, Robert A.; Katz, Jerome A.; Bagsby, Patricia G.
For entrepreneurs, being offered a distribution deal by Walmart seems like a dream come true. After all, what better way to have a new product quickly appear in thousands of stores all around the United States or maybe even all around the world? This dream became a reality for Marty, the creator of Tiny Sips—a simple, wholesome children's beverage made from Montana spring water and all-natural ingredients. As the details and conditions related to the distribution deal became apparent, however, Marty soon understood that doing business at that level requires sophisticated entrepreneurial savvy and a great deal of capital. The joy of possibly selling Tiny Sips everywhere suddenly became eclipsed by questions about how to raise enough cash to scale quickly while simultaneously minimizing risk. Marty needed to employ the business acumen necessary to slow down, consider the pros and cons, and make the best decision for his company. The educational focus of this case involves weighing the entrepreneurial risks and rewards of pursuing a deal with a large retailer like Walmart. While this type of opportunity may seem exciting at first glance, a variety of factors must be considered in order to find a thoughtful and sensible path forward.